Effects of computer-assisted instruction on the learning of angle properties of circles among upper secondary students - Ong, Mei Fen. (2008)
The primary focus of the research is to evaluate the effectiveness of Computer-Assisted Instruction (CAI) in the mathematics curriculum, specifically achievement and attitudes towards the learning of Angle Properties of Circles among upper secondary students.